2001
DOI: 10.1103/physrevlett.86.3084
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Resolved Local Variation of the Barrier Height of the Flip-Flop Motion of Single Buckled Dimers of Si(100)

Abstract: The dynamics of the flip-flop motion of single buckled dimers of Si(100) was elucidated by locating the tip of a scanning tunneling microscope over a single flip-flopping dimer and measuring the tunneling current (time trace). Based on a statistical analysis of the time trace, we succeeded in estimating the activation energy and the energy splitting between the two stable configurations of buckling. Strong dependence of the dynamics of the flip-flop motion on the local environment was found: Activation energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
62
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 14 publications
11
62
0
Order By: Relevance
“…They demonstrated that the tunneling current recorded above one of the atoms of a dimer of the Ge(001) surface exhibited telegraph like noise. A few years later similar experiments were reported for Si(001) by Hata et al [14], Yoshida et al [15], and Pennec et al [16]. The latter measurements demonstrated that the flip-flop motion of the dimers can be interpreted in terms of a so-called phason.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…They demonstrated that the tunneling current recorded above one of the atoms of a dimer of the Ge(001) surface exhibited telegraph like noise. A few years later similar experiments were reported for Si(001) by Hata et al [14], Yoshida et al [15], and Pennec et al [16]. The latter measurements demonstrated that the flip-flop motion of the dimers can be interpreted in terms of a so-called phason.…”
supporting
confidence: 50%
“…However, it has been well established since than that the lowest energy configuration is a buckled dimer [11,12]. The observed symmetric dimers are actually flip flopping rapidly between the two possible buckled configurations [13][14][15][16]. The first direct evidence for this flip-flop motion was provided by Sato, Iwatsuki, and Tochihara [13].…”
mentioning
confidence: 86%
“…9 This low temperature phase transition ͑around 40 K͒ was also observed by several other groups using STM, synchrotron-radiation photoelectron spectroscopy, and low-energy electron diffraction ͑LEED͒. [10][11][12] However, these later experiments disagree with the stable symmetric dimer inferred at 0 K by Kondo et al Instead, they suggest an asymmetric p(2ϫ1) phase, a p(2ϫ2) phase, or a disordered p(2ϫ1) phase due to the dynamic flip-flop motion of the buckled dimers at low ͑Ͻ40 K͒ temperatures.…”
Section: Introductionmentioning
confidence: 65%
“…In experiments, there have been numerous indications from spectroscopy, 6 diffraction, 7 and scanning tunneling microscopy ͑STM͒, [1][2][3]5,[9][10][11][12] that the dimers are intrinsically buckled above 100 K. The dominant appearance of the symmetric dimers in STM images at room temperature was ascribed to the dynamic flipping motion of the buckled dimers. The buckled dimers are observed predominantly at low temperatures ͑110-120 K͒.…”
Section: Introductionmentioning
confidence: 99%
“…Around 2000, I was conducting research on atomic structure analysis of semiconductor surfaces using the scanning tunneling microscope at Tsukuba University, and I went to the American Vacuum Society (the largest and most authoritative society in the field of surface science) to give a lecture presentation of my greatest finding during the preceding few years (this was later published in Physical Review Letter). [8] In a lecture hall having seating capacity of 300 that was normally filled with several hundred people, there were only ten people. Most of them were Japanese.…”
Section: Research Policy That Set the Direction And My Thoughtsmentioning
confidence: 99%